2012
DOI: 10.4103/0976-9668.95973
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of gliomatosis cerebri presenting as dementia

Abstract: Dementia with the onset before the age of 65 years is classified as early-onset dementia. Although uncommon, it has considerable impact on the lives of patients and care givers, alike. A substantial subset of patients may have underlying reversible causes. Yet, many, especially those of the very young may be initially misdiagnosed. A case of young woman with rapid mental decay is described here. She was finally diagnosed with gliomatosis cerebri (GC) involving only right frontal lobe. This atypical radiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…Ayrıca bu çalışmada baş ağrısı %39, nöbet %38, kranial nöropati %37, intrakranial basınç artışı %34 ve spinoserebellar defisit %33 sıklığında bildirilmiştir (1). Literatürde demans kliniği ile başvuran olgularda mevcuttur (6). Bizim olgumuz da kortikospinal trakt bulguları, bilinç değişiklikleri, mental fonksiyonlarda azalma ve fasial paralizi mevcuttu.…”
Section: Discussionunclassified
“…Ayrıca bu çalışmada baş ağrısı %39, nöbet %38, kranial nöropati %37, intrakranial basınç artışı %34 ve spinoserebellar defisit %33 sıklığında bildirilmiştir (1). Literatürde demans kliniği ile başvuran olgularda mevcuttur (6). Bizim olgumuz da kortikospinal trakt bulguları, bilinç değişiklikleri, mental fonksiyonlarda azalma ve fasial paralizi mevcuttu.…”
Section: Discussionunclassified
“…Gutch, et al reported that the clinical course of GC is typically slow and long, especially when the neoplastic infiltrate is of low histological grade [9].…”
Section: Pathologymentioning
confidence: 99%